2006
DOI: 10.1093/jos/ffl009
|View full text |Cite
|
Sign up to set email alerts
|

What Autism Can Reveal About Every ... not Sentences

Abstract: The sentence Every horse did not jump over the fence can be interpreted with the negation taking scope over the quantifier (i.e. not every horse jumped) or with the quantifier Every taking scope over the negation (ultimately providing the reading no horse jumped). Beginning with Musolino, Crain and Thornton (2000), much work has shown that while adults typically adopt a Not every reading in '2-of-3' contexts (e.g. where 2-of-3 horses jump over a fence), children do not and often produce None readings instead. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…It is worth noting that scalar implicature computation (and other pragmatic abilities—see Loukusa & Moilanen, 2009 for a review) has been investigated in adolescents and adults with autism spectrum disorder (ASD), a group that includes individuals with widely different cognitive and linguistic profiles who are generally known to have ToM deficits (Newschaffer et al, 2007). 2 In one study, ASD participants (who scored poorly on ToM measures of false belief) adopted pragmatically under‐informative descriptions of story‐book content more often than neurotypical controls, as anticipated by the hypothesis that ToM is involved in scalar implicature computation (Noveck, Guelminger, Georgieff, & Labruyere, 2007). Other studies have shown that ASD adolescents (Hochstein, Bale, & Barner, 2017; Pijnacker, Hagoort, Buitelaar, Teunisse, & Geurts, 2009) and adults (Chevallier, Wilson, Happé, & Noveck, 2010) are not impaired in their ability to compute implicatures.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that scalar implicature computation (and other pragmatic abilities—see Loukusa & Moilanen, 2009 for a review) has been investigated in adolescents and adults with autism spectrum disorder (ASD), a group that includes individuals with widely different cognitive and linguistic profiles who are generally known to have ToM deficits (Newschaffer et al, 2007). 2 In one study, ASD participants (who scored poorly on ToM measures of false belief) adopted pragmatically under‐informative descriptions of story‐book content more often than neurotypical controls, as anticipated by the hypothesis that ToM is involved in scalar implicature computation (Noveck, Guelminger, Georgieff, & Labruyere, 2007). Other studies have shown that ASD adolescents (Hochstein, Bale, & Barner, 2017; Pijnacker, Hagoort, Buitelaar, Teunisse, & Geurts, 2009) and adults (Chevallier, Wilson, Happé, & Noveck, 2010) are not impaired in their ability to compute implicatures.…”
Section: Introductionmentioning
confidence: 99%
“…Consider the ambiguous sentences below along with their potential paraphrases. Several studies on the acquisition of quantification have shown that when given a Truth Value Judgment Task (TVJT), preschoolers, unlike adults, display a strong preference for the isomorphic interpretation of sentences like (19-20) (Musolino (1998), Musolino et al (2000), Lidz and Musolino (2002), Musolino and Gualmini (2004), Noveck et al (2007), among others). This is what Musolino (1998) called "the observation of isomorphism".…”
Section: Isomorphism and The Scope Of Negationmentioning
confidence: 99%
“…Isomorphism effects have been found in several languages (Lidz & Musolino 2002, Noveck et al 2007, Han, Lidz & Musolino 2007 1 . Lidz and Musolino (2002) examined sentences containing a quantifier and negation in Kannada in order to determine whether isomorphism should be described in structural or linear terms.…”
Section: Isomorphism and The Scope Of Negationmentioning
confidence: 99%
“…Closer to home, might some children with cognitive disabilities come to this world expecting auditory, olfactory, or tactile modes of reasoning (cf. [11])? The ability to draw inferences may be an important marker of rationality, but ascribing a lack of such logical powers to an agent [5] will remain inconclusive as long as we have not essayed multiple kinds of logic.…”
Section: Introductionmentioning
confidence: 99%